Complications of deep infiltrating intestinal endometriosis - Bandeira, Carolina; Costa Filho, Anibal; Maia, Ana Cecília; Azevedo, Larissa Karen Silva Alves de; Ferreira, Maria Beatriz Batista; Gomes, Naftali Duarte do Bonfim; Medeiros, Camila Soares Barros Fernandes; Melo, Thalya da Nóbrega (Research, Society and Development, 2024)
Introduction: Deep infiltrating endometriosis (DIE) is one of the most severe manifestations of the disease, affecting the intestines in twenty-five percent of cases. Lesions can be solitary or multifocal, and symptoms vary widely. Objective: The aim of this article is to demonstrate the main complications caused by deep infiltrating intestinal endometriosis. Methodology: The research is based on a thorough literature review, selecting relevant and up-to-date articles from scientific databases. Results: The main symptoms observed in patients with DIE include dysmenorrhea, pelvic pain, deep dyspareunia, as well as intestinal symptoms such as diarrhea, tenesmus, hematochezia, and constipation. The most critical complications vary according to the extent of the lesions. The most commonly affected region is the rectosigmoid, followed by the appendix, cecum, and small intestine. Other significant complications include intestinal constipation (caused by slow progression of feces through the colon and rectum) and infertility. Conclusion: Although the complications of DIE are complex and numerous, certain surgical techniques and management approaches can be adopted to control both symptoms and complications, aiming to improve the quality of life for patients.